Difference Effectiveness of Progressive Muscle Relaxation Therapy and Endorphin Massage Therapy Towards Reducing Menstrual Pain Intensity in Adolescents - Pawestri Pawestri; Machmudah Machmudah; Sri Rejeki; Satriya Pranata; Savira Ayu Nur Fitria; Medina Laila Fitri; Reina Dhamanik; Nikmatul Khayati (Gonabad University of Medical Sciences, 2023)
Background: Problems arising during menstruation include pain before or during menstruation. Progressive muscle relaxation (PMR) techniques and endorphin massage (EM) therapy are effective in controlling menstrual pain. This study aims to determine the difference in the effectiveness of pain intensity carried out by PMR therapy and EM therapy.  Methods: This study was a quasi-experimental research with a two-group pretest and posttest design. Respondents were selected using a purposive sampling technique with inclusion and exclusion criteria. The inclusion criteria included students who experienced dysmenorrhea and do not have a genetic abnormality. The respondents who met the criteria were 80 respondents. The respondents were randomly selected using computerized to divide them into two groups. Forty respondents received PMR intervention and another 40 respondents received EM intervention. Bivariate analysis was performed using Wilcoxon test. Identification of respondents who fit the criteria, i.e. adolescents aged 13-14 years who experience menstrual pain, and do not have genetic abnormalities. Pain measurement was performed with a Numeric Rating Scale (NRS) and analyzed using the Mann-Whitney test.  Results: PMR is more effective in lower intensity painful menstruation compared to EM proven that the average painful menstruation after PMR was 2.42±0.675, while the average painful menstruation after EM was 2.90±0955 with a difference of 4.8 points with a significance level of 0.000. Menstrual pain can be reduced by blocking nerve impulses from reaching the brain, including PMR therapy to control tension and anxiety.  Conclusion: PMR therapy is more effective for controlling menstrual pain. PMR therapy can be done alone by adolescents when menstrual pain appears.